The THE CONNECTION BETWEEN INTERPRETATION AND LOCAL CULTURE: The Meaning of Jihad Verses in the Sundanese Interpretation of “Ayat Suci Lenyepaneun” in an Effort to Religious Moderation - Azkia Falsa Annaba (Institut Agama Islam Persis Bandung, 2023)
Azkia Falsa Annaba. THE CONNECTION BETWEEN INTERPRETATION AND LOCAL CULTURE: The Meaning of Jihad Verses in the Sundanese Interpretation of “Ayat Suci Lenyepaneun” in an Effort to Religious Moderation. This bachelor thesis analyzes the relationship between interpretation and local culture in the context of Islam, especially regarding the interpretation of jihad verses in texts